The Current Role and Future Development of Unmanned Aerial Vehicles in Cartography and Geodesy - Mustofoyev Elnur Nurbek o‘g‘li (Scientific Trends, 2025)
This article analyzes the application of Unmanned Aerial Vehicles (UAV) in cartography and geodesy, highlighting their advantages and future development. UAVs enable the creation of accurate maps, updating topographic data, conducting geodetic measurements, and carrying out ecological monitoring. The article discusses how UAVs equipped with high-precision cameras, LiDAR systems, and GPS technology allow for quick and efficient data collection, as well as the advantages they provide over traditional methods. Additionally, the growth indicators of UAV usage in cartography and geodesy, along with their economic efficiency, are also examined.
Keywords: UAVs, cartography, geodesy, aerophotogrammetry, LiDAR, GPS, topographic maps, geodetic accuracy, digital surface models (DSM), high-resolution cameras, ecological monitoring, natural disasters, GIS systems, urban planning, innovations.